Root phenology in an Arctic shrub-graminoid community: the effects of long-term warming and herbivore exclusion. Issue 1 (December 2016) - Radville, Laura; Post, Eric; Eissenstat, David
Abstract Background Shifts in phenology have been widely reported in response to global warming and have strong effects on ecosystem processes and greenhouse gas emissions. It is well documented that warming generally advances many phenophases of aboveground plant phenology, but its influence on root phenology is unclear. Most terrestrial biosphere models assume that root and shoot growth occur at the same time and are influenced by warming in the same manner, but recent studies suggest that this may not be the case. Testing this assumption is particularly important in the Arctic where over 70 % of plant biomass can be belowground and warming is happening faster than in other ecosystems. Herbivory may mediate the impacts of warming, and carbon removal from grazing may alter carbon available for root growth. In 2013 and 2014 we examined the timing of root growth in Arctic shrub-graminoid communities in a fully factorial design of plots that were warmed or ambient and excluded or permitted access by large herbivores. Results Peak root growth occurred two and one half weeks before leaf growth, suggesting that spring root phenology is not controlled by carbon produced during spring photosynthesis. This may uncouple spring root phenology from spring shoot phenology. Consistent with such uncoupling, spring leaf cover was advanced by warming and delayed by herbivory, but neither treatment significantly affected root phenology. Root growth was not driven by soil temperature, and occurred in near-freezing temperatures above the permafrost. Additionally, summer root production appeared to be linked to soil moisture at this relatively dry site, and autumn phenology was not driven by photoperiod as previous studies have suggested. Conclusions Root phenology was not directly driven by temperature in this system, promoting differential above- and belowground phenological responses to warming and herbivore exclusion. Aboveground phenology, one of the most widely measured aspects of climate change, may not represent whole-plant phenology or indicate the timing of whole-plant carbon fluxes as commonly assumed.